2022
DOI: 10.56499/jppres22.1452_10.5.905
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antimicrobial activity of an active plant-based quadrocomplex for skin hygiene

Abstract: Context: The current epidemiological situation causes a new surge of interest to perspective antimicrobial formulations for proper skin hygiene. Aims: To evaluate in vitro and in vivo the antimicrobial activity of a novel active quadrocomplex (QC) for skin hygiene based on Melaleuca alternifolia essential oil, eucalyptol, (-)-α-bisabolol and silver citrate. In addition, to analyze the phytochemical constituents by gas chromatography-mass spectrometry (GC-MS) and to assess the skin irritant potential after regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…A complex based on natural antimicrobial and anti-irritant compounds, constituted by TTO (0.3%), eucalyptol (0.15%), α-bisabolol (0.10%), and silver citrate (0.01%) in specific ratio 30:15:10:1, respectively was mixed with soap base ingredients and tested for skin hygiene [ 101 ]. The antimicrobial activity was determined against the following microorganisms: Bacillus cereus ATCC 10702, S. epidermidis ATCC 14990, S. aureus ATCC 6538-P or ATCC 29213, E. coli ATCC 25922 and P. aeruginosa ATCC 9027, Micrococcus luteus 10240a, and C. albicans ATCC 10231.…”
Section: Biological Properties Of Ttomentioning
confidence: 99%
See 1 more Smart Citation
“…A complex based on natural antimicrobial and anti-irritant compounds, constituted by TTO (0.3%), eucalyptol (0.15%), α-bisabolol (0.10%), and silver citrate (0.01%) in specific ratio 30:15:10:1, respectively was mixed with soap base ingredients and tested for skin hygiene [ 101 ]. The antimicrobial activity was determined against the following microorganisms: Bacillus cereus ATCC 10702, S. epidermidis ATCC 14990, S. aureus ATCC 6538-P or ATCC 29213, E. coli ATCC 25922 and P. aeruginosa ATCC 9027, Micrococcus luteus 10240a, and C. albicans ATCC 10231.…”
Section: Biological Properties Of Ttomentioning
confidence: 99%
“…The antimicrobial activity was determined against the following microorganisms: Bacillus cereus ATCC 10702, S. epidermidis ATCC 14990, S. aureus ATCC 6538-P or ATCC 29213, E. coli ATCC 25922 and P. aeruginosa ATCC 9027, Micrococcus luteus 10240a, and C. albicans ATCC 10231. The combination displayed additive or synergistic activities against most strains studied, and a balanced performance between antimicrobial activity and biological safety, without skin irritant potential [ 101 ].…”
Section: Biological Properties Of Ttomentioning
confidence: 99%
“…The substance of plant origin enriched with M. alternifolia essential oil, 1,8-cineole and (-)-α-bisabolol at a specific chosen ratio of 1:1:1 was previously investigated for the balancing of the skin microflora [11] and incorporated into the shampoo formulation C. The tested shampoo formulation contained M. alternifolia essential oil, 1,8-cineole and (-)-αbisabolol at a concentration of 0.25%, 0.25% and 0.25%, respectively. The results showed that this shampoo formulation inhibited the growth of standard strains of microorganisms compared to the formulations with antifungal substances recommended for the treatment of SD (Table 3).…”
Section: Evaluation Of the Antimicrobial Effect For Shampoo With The ...mentioning
confidence: 99%
“…Plant-based substances, such as essential oils or plant extracts, have comprehensive compositions, multiple properties, different activities and low irritancy potential [10]. In an investigation by the authors, the synergetic combination of Melaleuca alternifolia (M. alternifolia) leaf oil, 1,8-cineole (eucalyptol) and (-)-α-bisabolol in a ratio of 1:1:1 was found to exhibit a documented therapeutic antimicrobial potential against pathogenic microflora related to SD [11].…”
Section: Introductionmentioning
confidence: 99%
“…The novel substance based on Melaleuca alternifolia (M. alternifolia) leaf oil (TTO), 1,8-cineole (eucalyptol), and (−)-α-bisabolol in a specific mass ratio of 1:1:1 was developed and investigated for the treatment of SD [4]. This targeted substance has a synergetic antimicrobial activity against Malassezia species, Staphylococcus epidermidis, and Staphylococcus aureus, which are related to the exacerbation of SD [4,16,17]. The antimicrobial potential of this combination was comparable to clinically recommended benzalkonium chloride [18,19], climbazole [20][21][22], and ketoconazole [6,[23][24][25] without damage of the normal scalp microflora [4,17].…”
Section: Introductionmentioning
confidence: 99%